Bilateral Vertebral Venous Sinus Thrombosis Causing Cervical Spinal Cord Compression in a Dog - Rhue, Kathryn E.; Taylor, Amanda R.; Cole, Robert C.; Winter, Randolph L. (Frontiers in Veterinary Science, 2017)
A 10-year-old male neutered mixed breed dog was evaluated for cervical hyperesthesia and tetraparesis. Magnetic Resonance A 10-year-old male neutered mixed breed dog was evaluated for cervical hyperesthesia and tetraparesis. Magnetic Resonance Imaging of the brain and cervical spinal cord identified an extradural compressive lesion over the body of C2 caused by marked dilation of the vertebral venous sinuses. Following intravenous contrast administration both vertebral sinuses had heterogeneous contrast enhancement consistent with incomplete thrombi formation. An abdominal ultrasound also showed a distal aortic thrombus. A definitive cause for the thrombi formation was not identified, but the patient had several predisposing factors which may have contributed. The patient was treated with a combination of warfarin, clopidogrel, and enoxaparin as well as analgesics. Within 48 hours of initiation of warfarin therapy the tetraparesis and hyperesthesia were markedly improved. Repeat abdominal ultrasound 3 weeks after discharge showed reduction in size of aortic thrombus. Neurologic function remained normal 6 weeks following initiation of treatment. Seventy-four days following initial diagnosis the patient rapidly declined and passed away at home. Necropsy was declined. This is the first report of vertebral venous sinus enlargement leading to spinal cord compression and tetraparesis in a dog. Additionally warfarin in combination with clopidogrel and enoxaparin appeared to be a safe and effective treatment for the suspected thrombi reported in this case. Vertebral sinus enlargement secondary to thrombi should be considered as a differential diagnosis in patients presenting with tetraparesis and cervical hyperesthesia.